Parametric Comparison of Selected Dual Elements PIR Sensors - Faisal Rafique; Najeeb Siddiqui (Sir Syed University Research Journal of Engineering and Technology)
Most of the warm blooded animals emanate thermal radiations in the MWIR to LWIR (Medium Wave to Long Wave Infrared) range from 3μm to 18μm. If the object is warmer than the surroundings, its thermal radiation is shifted toward higher frequency within the band and the thermal flux rate becomes stronger. To detect radiation in this band, single and multi-elements pyroelectric sensors utilized in the scanning systems to detect, with background contrast, the presence of still or moving thermal objects emitting thermal flux in the bandwidth specified. PIR sensors are commonly used to detect these radiation, their response is further processed by electronic systems and generally analyzed by software embedded systems. Here we present a comparative study of commercially available PIR sensors. In this study we evaluated dual element PIR sensors for their electrical and thermal parameters. Two types of test procedures were used, which can be used for any type of PIR sensors.